Cold rolling production process for rolling titanium strip in short process
Through the cold rolling production process of titanium strip rolling, vacuum self-consumed arc smelting and β-stabilized elements are used to improve the material structure, solving the problems of low production efficiency and unstable quality in traditional processes, and achieving high efficiency and energy-saving Titanium strip production.
Patent Information
- Application Number
- CN202411204844.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-30
- Publication Date
- 2024-12-27
AI Technical Summary
The production process of traditional titanium strips is long and has high energy consumption, resulting in unstable product quality and low production efficiency. The existing short-process cold rolling technology is difficult to solve the problem of work hardening and surface quality.
The cold rolling production process of titanium strips using short-process rolling, including preparation of blanks, sintering rough rolling and cold rolling treatment, removing impurities through vacuum consumable arc smelting, precisely controlling the pressing and annealing parameters, and using β-stabilized elements and packages The material improves the material structure, gradually reduces the amount of cold rolling deformation, and improves the material uniformity and mechanical properties.
Shorten the production cycle, improve the mechanical properties and surface quality of titanium strips, reduce production costs, and is suitable for the production of titanium strips of various specifications, achieving rapid and energy-saving and efficient production.
Smart Images

Figure CN119194142A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of titanium strip preparation, and in particular to a short-process cold rolling production process for rolling titanium strips. Background Art
[0002] With the growing demand for high-performance materials in aerospace, chemical industry, medical equipment and other fields, titanium and its alloys have attracted widespread attention due to their excellent mechanical properties, corrosion resistance and biocompatibility. As one of the important forms of titanium alloy, the production process of titanium strip directly affects the quality and performance of the product.
[0003] The traditional titanium strip production process often involves multiple heat treatments and rolling, which is long, energy-intensive, and has a long production cycle. As the market's requirements for titanium strip quality stability and production efficiency increase, the research and development of an efficient, energy-saving, short-process cold rolling production process has become the focus of the industry.
[0004] The conventional short-process cold rolling process is to perform low-temperature rolling by optimizing the rolling path, but the existing short-process cold rolling technology still has shortcomings. The short-process cold rolling process usually leads to serious work hardening problems in the production of titanium strip, and the surface quality of the finished strip is poor. This problem cannot be solved by changing the rolling path. Extending the annealing and rolling operations to improve the quality of titanium strip will complicate the rolling process and is not conducive to the implementation of rapid production. Summary of the invention
[0005] In order to solve the above problems, the present invention provides a short-process cold rolling production process for rolling titanium strips.
[0006] The technical solution of the present invention is: a short-process cold rolling production process for rolling titanium strip, comprising the following steps:
[0007] S1. Preparation of blocks
[0008] Prepare titanium metal raw materials, load them into the mold, press them at a pressure of 25-35MPa, and hold the pressure for 30-50s. After the pressure holding is completed, remove the mold to obtain a blank;
[0009] S2, sintering rough rolling
[0010] Grinding and welding the plurality of said blanks, and then vacuum sintering to obtain sintered blanks, and then using the sintered blanks as electrodes for vacuum consumable arc melting, and rough rolling to obtain slabs with a thickness of 4 to 8 mm;
[0011] S3, cold rolling treatment
[0012] The sheet is annealed at a temperature of 650-750° C. for 4-6 hours, and then pickled to obtain a coil. The coil is then cold rolled for 6-11 passes to obtain a thin coil. The thin coil is degreased and stretched and leveled to obtain a finished titanium strip.
[0013] Description: The present invention processes the raw materials first in the entire process flow, and then uses heat treatment and cold processing steps to enhance the uniformity of the materials, which can improve the mechanical properties and surface quality of the titanium strip and improve production efficiency while shortening the rolling process; through vacuum consumable arc melting, impurities can be effectively removed, the purity of the material can be improved, and the loss of the material in the melting process can be reduced; by accurately controlling parameters such as pressing pressure, holding time, sintering temperature and time, the production cost can be effectively controlled while ensuring product quality; this process flow is suitable for the production of titanium strips of various specifications and requirements, and has strong flexibility and adaptability; the production cycle can be shortened by simplifying the cold rolling process. Since cold rolling will affect the elasticity of the titanium strip, shortening the cold rolling process will reduce the quality of the titanium strip. By processing the raw materials, the quality of the final product can still be guaranteed.
[0014] Furthermore, the method for preparing the blank described in S1 comprises: S1-1, mixing, by mass percentage, 0.2-5% of molybdenum powder, 0.5-5% of vanadium powder, 0.5-2% of niobium powder and the remainder of titanium sponge to obtain a metal mixed powder;
[0015] S1-2, dividing an aluminum foil sheet accounting for 3-6% of the mass ratio of the titanium sponge into two equal parts, and wrapping the two aluminum foil sheets with 0.2-1% of tin powder, 0.2-0.8% of zirconium powder, and 0.2-0.6% of hafnium powder, accounting for the mass ratio of the titanium sponge, to obtain two packages;
[0016] S1-3, divide the metal mixed powder into three parts, and the mass ratios of the three parts of the metal mixed powder are: 0.3~0.7:1:0.3~0.7; introduce the first part of the metal mixed powder evenly into the mold, then add a part of the bagging material, and then evenly spread the second part of the metal mixed powder, and then add another part of the bagging material, and finally add the third part of the metal mixed powder; after pressing and forming, remove the mold to obtain a blank.
[0017] Description: Through a one-time pressing process, the need for multiple heating and cooling is reduced, thereby shortening the production cycle; the continuous process reduces the waiting time between processes and improves production efficiency; the addition of β-stabilizing elements such as molybdenum, niobium, and vanadium can enable the titanium strip to maintain good plasticity and toughness after short-process cold rolling, improve the strength and hardness of the titanium alloy, and help reduce defects such as pores inside the billet, thereby enhancing the quality of the titanium strip;
[0018] The aluminum foil in the package can compensate for the excessive hardening of the titanium strip caused by short-process cold rolling. The reduction effect of aluminum can remove impurities and deoxidize the titanium on the contact surface with the aluminum foil, increase the purity of the titanium on the contact surface with the aluminum foil, reduce the hardness, and strengthen the bonding of the organization. The appropriate addition of interstitial elements tin, zirconium, and hafnium in the aluminum foil can significantly affect the physical and chemical properties of alumina. Tin, zirconium, and hafnium exist in the form of dopants, replacing or entering the interstitial positions in the alumina lattice, changing the microstructure and electronic structure of the material. As a metal element, tin has a large atomic radius and can hinder the migration path of some atoms on the surface of alumina, increase its dispersibility, and have little effect on the peak temperature and peak intensity of the high-temperature reduction peak. Zirconium and alumina work synergistically with each other to improve the hardness and fracture toughness of the reduced alumina foil and reduce its brittleness. The addition of hafnium to alumina can improve the mechanical properties of the material. By precisely controlling the content of these elements, the comprehensive performance of titanium strip can be improved without sacrificing the toughness of the material.
[0019] Furthermore, the particle size of the molybdenum powder in S1-1 is 5 to 15 mm, the particle size of the vanadium powder is 4 to 8 mm; the particle size of the niobium powder is 3 to 6 mm; and the particle size of the sponge titanium is 5 to 10 mm.
[0020] Description: Appropriate particle size distribution helps the powder flow and fill the mold better during the pressing process, thereby achieving higher density and better compactness during the sintering process, reducing defects inside the material, and improving the mechanical strength and corrosion resistance of the product; uniform particle size distribution helps improve the material's fatigue resistance, wear resistance, and impact resistance; appropriate particle size can help the reaction be more uniform, avoid local overheating or incomplete reaction, and obtain higher precision and surface finish during processing. Uniform particle size distribution helps the material remain stable at high temperatures and prevent cracks or deformation caused by uneven thermal expansion.
[0021] Furthermore, the size of the package material in S1-2 matches the size inside the mold; the particle size of the tin powder is 0.5-2 mm; and the particle sizes of the zirconium powder and hafnium powder are both 0.5-3 mm.
[0022] Note: Smaller particles can be arranged more closely, reducing the porosity inside the material. The size of the package is close to the size inside the mold, which increases the scope of action of the package in the block.
[0023] Furthermore, the sintering temperature of the vacuum sintering in S2 is 1800-2200°C, and the vacuum degree is 0.1-1×10 - 2 Sintering under Pa conditions for 5 to 8 hours.
[0024] Description: The vacuum environment can effectively remove impurities and gases during the sintering process. Appropriate sintering temperature and vacuum degree are conducive to the uniform growth of material grains and improve the mechanical properties of the material. Vacuum sintering helps the atomic migration inside the material, thereby improving the density and mechanical strength of the material.
[0025] Furthermore, the arc length of the vacuum consumable arc melting in S2 is controlled to be 160-180 mm, the melting current is 4000-5000 A, the melting voltage is 35-55 V, and the melting speed is 4-5 kg / min.
[0026] Note: By adjusting the smelting current and voltage, the melting rate of the metal and the temperature of the molten pool can be controlled, thereby optimizing the smelting effect; the appropriate smelting speed helps to improve production efficiency while ensuring the quality of the ingot.
[0027] Furthermore, the coil cold rolling in S3 is carried out by a twenty-roller cold rolling mill; and the deformation amount of the first pass is 25-35%, and the deformation amount of each subsequent pass decreases gradually, and the minimum deformation amount of the pass is 15-17%.
[0028] Description: Through gradually decreasing deformation, the stress distribution of the material during the cold rolling process can be made more uniform, reducing material damage and uneven deformation caused by stress concentration; appropriate deformation can promote the refinement of the internal grains of the material and improve the mechanical properties of the material, such as strength and toughness; gradually decreasing deformation helps to reduce cracks and defects in the material during the cold rolling process and improve the yield rate; the twenty-roll cold rolling mill has good plate shape control ability and is suitable for cold rolling processing of a variety of materials, which can improve the surface flatness and smoothness of the coil; reasonable pass deformation design can reduce energy consumption during cold rolling and improve production efficiency; it can effectively improve the quality and processing efficiency of titanium strips and meet high-standard industrial application requirements.
[0029] Furthermore, the annealing in S3 is carried out in an argon atmosphere, and the pressure in the furnace is 2-4 KPa and the argon flux is 30-50 m 3 / h, the pressure in the furnace is 0.8~1.2KPa and the argon flux is 15~25m 3 / h.
[0030] Description: Argon can effectively prevent the oxidation reaction of materials at high temperatures and maintain the chemical purity of materials; argon atmosphere can reduce the contamination of external impurities on the surface of materials, especially during the annealing process, it can prevent the material from absorbing gas impurities; by adjusting the pressure in the furnace and the argon flux, the annealing atmosphere can be accurately controlled to provide a stable annealing environment for the material; appropriate argon flux helps to evenly distribute heat in the furnace, so that the material can be evenly heated, thereby achieving a uniform annealing effect.
[0031] Furthermore, the cold rolling speed is 100-120 m / min; the degreasing temperature is 50-70°C.
[0032] Description: Faster rolling speed can shorten the production cycle, increase the output per unit time, and thus improve the overall production efficiency; fast rolling can reduce the energy consumption in the rolling process, because the rolling time is short and the required heat and electricity are relatively small; fast rolling helps to maintain the mechanical properties of the material, because the material stays at a high temperature for a short time and is not prone to excessive hardening or other adverse microstructural changes; a degreasing temperature of 50-70°C can effectively remove the grease remaining in the rolling process to prevent these greases from causing contamination or adverse reactions during subsequent heat treatment; a lower degreasing temperature helps to protect the material surface from damage, avoid oxidation or other chemical reactions caused by high temperature, and maintain the surface quality of the material.
[0033] The beneficial effects of the present invention are:
[0034] In the whole process of the present invention, the raw materials are first processed, and then heat treatment and cold working steps are used to refine the grains, improve the microstructure of the material, enhance the uniformity of the material, and improve the mechanical properties and surface quality of the titanium strip; through vacuum consumable arc melting, impurities can be effectively removed, the purity of the material can be improved, and the loss of the material in the melting process can be reduced; the continuous cold rolling process is used to greatly improve the production efficiency, shorten the time of other processes, and is suitable for large-scale production;
[0035] By shortening the overall cold rolling process and improving the structure of the billet itself before short-process low-temperature rolling, continuous and rapid production of titanium strip can be achieved, and the problem of severe work hardening of titanium strip usually caused by the short-process cold rolling process can be avoided. The surface quality of the finished strip can be improved while achieving rapid production. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 is a bar graph of the tensile strength of samples of Examples 1 to 7, Examples 17 and 18, and Comparative Examples 1 to 8 of the present invention;
[0037] Figure 2 It is a bar graph of the yield strength of samples of Examples 1 to 7, Examples 17 and 18, and Comparative Examples 1 to 8 of the present invention;
[0038] Figure 3 It is a bar graph of the elongation of samples of Examples 1 to 7, Examples 17 and 18, and Comparative Examples 1 to 8 of the present invention. DETAILED DESCRIPTION
[0039] In order to further illustrate the method adopted by the present invention and the effect achieved, the technical solution of the present invention will be clearly and completely described in combination with experiments below.
[0040] Embodiment 1: A short-process cold rolling production process for titanium strip, comprising the following steps:
[0041] S1. Preparation of blocks
[0042] S1-1, by mass percentage, 2.4% of molybdenum powder, 2.25% of vanadium powder, 1.25% of niobium powder and the remainder of titanium sponge are mixed to obtain a metal mixed powder;
[0043] S1-2, dividing an aluminum foil sheet accounting for 1.5% of the mass ratio of the titanium sponge into two equal parts, and wrapping the two aluminum foil sheets with 0.4% of tin powder, 0.5% of zirconium powder and 0.4% of hafnium powder accounting for the mass ratio of the titanium sponge, respectively, to obtain two packages;
[0044] S1-3, the metal mixed powder is divided into three parts, and the mass ratios of the three parts of the metal mixed powder are: 1:5:1; the first part of the metal mixed powder is evenly introduced into the mold, and then a part of the bagging material is added, and then the second part of the metal mixed powder is evenly spread, and then another part of the bagging material is added, and finally the third part of the metal mixed powder is added; the pressure of 30MPa is used for pressing, and the pressing and holding time is 40s. After the holding pressure is completed, the mold is removed to obtain a blank;
[0045] The particle size of the molybdenum powder is 10mm, the particle size of the vanadium powder is 6mm; the particle size of the niobium powder is 4.5mm; the particle size of the titanium sponge is 7.5mm; the size of the package material matches the size inside the mold; the particle size of the tin powder is 8mm; the particle sizes of the zirconium powder and hafnium powder are both 1.25mm;
[0046] The sintering temperature of the vacuum sintering is 2000°C, and the vacuum degree is 0.5×10 -2 Sintering at 370°C for 6.5 h at 400°C.
[0047] S2, sintering rough rolling
[0048] Grinding and welding the ends of several of the blanks, and then vacuum sintering to obtain sintered blanks, and then using the sintered blanks as electrodes for vacuum consumable arc melting, and obtaining slabs with a thickness of 6 mm after rough rolling; the arc length of the vacuum consumable arc melting is controlled to be 170 mm, the melting current is 4500 A, the melting voltage is 45 V, and the melting speed is 4.5 kg / min;
[0049] S3, cold rolling treatment
[0050] The sheet is annealed at a temperature of 700° C. for 5 hours, and then pickled to obtain a coil, and then the coil is cold-rolled for 9 passes to obtain a thin coil; the thin coil is degreased, and the titanium strip is obtained after being stretched and leveled;
[0051] The coil cold rolling is carried out by a twenty-roller cold rolling mill; the deformation amount of the first pass is 30%, and the deformation amount of each subsequent pass decreases gradually, and the minimum deformation amount of the pass is 16%;
[0052] The annealing was carried out in an argon atmosphere, with a furnace pressure of 3 KPa and an argon flux of 40 m 3 / h, the furnace pressure during the insulation and cooling process is 1KPa, and the argon flux is 20m 3 / h; the cold rolling speed is 110m / min; the degreasing temperature is 60°C.
[0053] Example 2: This example is basically the same as Example 1, except that, by mass percentage, 0.2% of molybdenum powder, 0.5% of vanadium powder, 0.5% of niobium powder and the remainder of sponge titanium are mixed to obtain a metal mixed powder.
[0054] Example 3: This example is basically the same as Example 1, except that, by mass percentage, 5% of molybdenum powder, 5% of vanadium powder, 2% of niobium powder and the remainder of sponge titanium are mixed to obtain a metal mixed powder.
[0055] Example 4: This example is basically the same as Example 1, except that an aluminum foil accounting for 3% of the mass ratio of the titanium sponge is divided into two equal parts, and the two aluminum foils are respectively wrapped with 0.2% of tin powder, 0.2% of zirconium powder and 0.2% of hafnium powder accounting for the mass ratio of the titanium sponge to obtain two packages.
[0056] Example 5: This example is basically the same as Example 1, except that an aluminum foil accounting for 6% of the mass ratio of the titanium sponge is divided into two equal parts, and the two aluminum foils are respectively wrapped with 1% of tin powder, 0.8% of zirconium powder and 0.6% of hafnium powder, accounting for 1% of the mass ratio of the titanium sponge, to obtain two packages.
[0057] Example 6: This example is basically the same as Example 1, except that the mass ratios of the three parts of metal mixed powder are 0.3:1:0.3 respectively.
[0058] Example 7: This example is basically the same as Example 1, except that the mass ratios of the three parts of metal mixed powder are 0.7:1:0.7 respectively.
[0059] Example 8: This example is basically the same as Example 1, except that a pressure of 25 MPa is used for pressing, and the pressing and holding time is 30 seconds.
[0060] Example 9: This example is basically the same as Example 1, except that a pressure of 35 MPa is used for pressing, and the pressing and holding time is 50 s.
[0061] Example 10: This example is basically the same as Example 1, except that the particle size of the molybdenum powder is 5 mm, the particle size of the vanadium powder is 4 mm; the particle size of the niobium powder is 3 mm; and the particle size of the sponge titanium is 5 mm.
[0062] Example 11: This example is basically the same as Example 1, except that the particle size of the molybdenum powder is 15 mm, the particle size of the vanadium powder is 8 mm; the particle size of the niobium powder is 6 mm; and the particle size of the sponge titanium is 10 mm.
[0063] Example 12: This example is basically the same as Example 1, except that the sintering temperature of the vacuum sintering in S2 is 1800°C and the vacuum degree is 0.1×10 -2 Pa and sintered for 5 hours; the arc length of the vacuum consumable arc melting was controlled to be 160 mm, the melting current was 4000 A, the melting voltage was 35 V, and the melting speed was 4 kg / min.
[0064] Example 13: This example is basically the same as Example 1, except that the sintering temperature of the vacuum sintering in S2 is 2200°C and the vacuum degree is 1×10 -2 Pa for 8 hours; the arc length of the vacuum consumable arc melting is controlled to be 180 mm, the melting current is 5000 A, the melting voltage is 55 V, and the melting speed is 5 kg / min.
[0065] Example 14: This example is basically the same as Example 1, except that the sheet is annealed at a temperature of 650°C for 4 hours, and then pickled to obtain a coil, which is then cold-rolled for 6 passes to obtain a thin coil; the deformation of the coil in the first cold rolling pass is 25%, and the deformation in each subsequent pass decreases gradually, with the lowest deformation being 15%.
[0066] Example 15: This example is basically the same as Example 1, except that the sheet is annealed at a temperature of 750°C for 6 hours, and then pickled to obtain a coil, which is then cold-rolled 11 times to obtain a thin coil; the deformation of the coil in the first cold rolling pass is 35%, and the deformation in each subsequent pass decreases gradually, with the lowest deformation being 17%.
[0067] Example 16: This example is basically the same as Example 1, except that during the heating process, the pressure in the furnace is 2 KPa and the argon flux is 30 m 3 / h, the pressure in the furnace is 0.8KPa and the argon flux is 15m 3 / h; the cold rolling speed is 100m / min; the degreasing temperature is 50°C.
[0068] Example 17: This example is basically the same as Example 1, except that the particle size of the tin powder is 0.5 mm; the particle sizes of the zirconium powder and hafnium powder are both 0.5 mm.
[0069] Example 18: This example is basically the same as Example 1, except that the particle size of the tin powder is 2 mm; the particle sizes of the zirconium powder and hafnium powder are both 3 mm.
[0070] Comparative Example 1: Example 1 is used as a reference, except that the raw material is not equipped with metal mixed powder, and only sponge titanium with a particle size of 7.5 mm is used.
[0071] Comparative Example 2: Example 1 is used as a reference, except that 6% of molybdenum powder, 7% of vanadium powder, 3% of niobium powder and the remainder of sponge titanium are mixed to obtain a metal mixed powder.
[0072] Control Example 3: Example 1 is used as a reference, except that an aluminum foil sheet accounting for 8% of the mass ratio of the titanium sponge is divided into two equal parts, and the two aluminum foil sheets are respectively wrapped with 3% of tin powder, 1% of zirconium powder and 1% of hafnium powder accounting for the mass ratio of the titanium sponge to obtain two packages.
[0073] Control Example 4: Using Example 1 as a reference, the difference is that the metal mixed powder is divided into three parts, and the mass ratios of the three parts of the metal mixed powder are 1:1:1 respectively.
[0074] Comparative Example 5: The particle size of the molybdenum powder is 16 mm, the particle size of the vanadium powder is 9 mm; the particle size of the niobium powder is 7 mm; and the particle size of the titanium sponge is 11 mm.
[0075] Comparative Example 6: The particle size of the molybdenum powder is 4 mm, the particle size of the vanadium powder is 3 mm; the particle size of the niobium powder is 2 mm; and the particle size of the titanium sponge is 4 mm.
[0076] Comparative Example 7: The particle size of the tin powder is 0.1 mm; the particle sizes of the zirconium powder and the hafnium powder are both 0.1 mm.
[0077] Comparative Example 8: The particle size of the tin powder is 3 mm; the particle sizes of the zirconium powder and hafnium powder are both 4 mm.
[0078] The samples produced in Examples 1 to 7, Examples 17 and 18 and Comparative Examples 1 to 8 were tested, and their performance changes were recorded. The tensile strength, yield strength and elongation of the titanium strip at room temperature were tested according to GB / T 228-2002.
[0079] The specific research is as follows:
[0080] 1. Explore the influence of metal powder ratio in raw materials S2 on the performance of titanium strip products:
[0081] like Figures 1 to 3 As shown, by comparing Examples 1 to 3, it can be seen that the tensile strength and yield strength of the titanium strip product sample produced in Example 1 are the largest, the tensile strength and yield strength of Example 2 are smaller than those of Example 1, the elongation performance of the titanium strip product sample produced in Example 1 is the best, and the elongation of Example 3 is slightly lower than that of Example 2;
[0082] Comparing Example 1 with Control Example 1, the tensile strength and yield strength of Control Example 1 are significantly smaller, and the elongation performance is significantly worse. It can be seen that the raw material ratio using this method has a positive effect on the production of titanium strip; comparing Example 1 with Control Example 2, Example 1 has better performance; this shows that the change in the raw material ratio in S1 has an impact on the toughness, elasticity and hardness properties of the titanium strip product, among which the process values used in Example 1 are the best.
[0083] 2. Explore the influence of the ratio of S2 packaging materials on the performance of titanium strip products:
[0084] like Figures 1 to 3 As shown, by comparing Examples 1, 4, and 5, it can be seen that the tensile strength and yield strength of the titanium strip product sample produced in Example 1 are the largest, and its elongation is the best. The elongation of Example 5 is slightly lower than that of Example 4, and the tensile strength and yield strength of Example 4 are lower than those of Example 5. It can be seen that the ratio of the packaging material can have a certain influence on the tensile strength, yield strength and elongation of the titanium strip product. Compared with Examples 4 and 5, the process value adopted in Example 1 is the best; the comprehensive performance of Comparative Example 3 is significantly lower than that of Examples 1, 4, and 5, and it is better to adopt the parameter range of this scheme for ratioing.
[0085] 3. Explore the influence of the introduction ratio of metal powder mixture when filling the mold in S3 on the performance of titanium strip products:
[0086] like Figures 1 to 3 As shown, by comparing Examples 1, 6, and 7, it can be seen that the tensile strength and yield strength of the titanium strip product sample produced in Example 1 are the largest, and its elongation is the best. The tensile strength and yield strength of Example 6 are higher than those of Example 7, and the elongation of Example 6 can be higher than that of Example 7. It can be seen that the introduction ratio of the metal mixed powder when filling the mold can have a certain influence on the tensile strength, yield strength and elongation of the titanium strip product. Compared with Examples 6 and 7, the process values used in Example 1 are the best; the comprehensive performance of Comparative Example 4 is significantly lower than that of Examples 1, 6, and 7. It can be seen that it is better to use the parameter range of this scheme for proportioning.
[0087] 4. Explore the effect of the particle size of the metal powder used in S2 on the performance of titanium strip products:
[0088] like Figures 1 to 3As shown, by comparing Examples 1, 17, and 18, it can be seen that the titanium strip product sample produced in Example 1 has the largest tensile strength and yield strength, and the best elongation. Using the particle size parameters of Example 1, its tensile strength and yield strength are significantly better, and the difference in elongation is not obvious. It can be seen that the particle size selection of the metal powder has a certain influence on the performance of the product; the comprehensive performance of Comparative Examples 5 to 8 is significantly lower than that of Examples 1, 17, and 18. It can be seen that the titanium strip finished product obtained by using the particle size parameters of this scheme has better performance.
Claims
1. A short-process cold rolling production process for titanium strip, characterized in that: The following steps are involved: S1. Preparation of blocks Prepare titanium metal raw materials, load them into the mold, press them at a pressure of 25-35MPa, and hold the pressure for 30-50s. After the pressure holding is completed, remove the mold to obtain a blank; S2, sintering rough rolling Grinding and welding the plurality of said blanks, and then vacuum sintering to obtain sintered blanks, and then using the sintered blanks as electrodes for vacuum consumable arc melting, and rough rolling to obtain slabs with a thickness of 4 to 8 mm; S3, cold rolling treatment The sheet is annealed at a temperature of 650-750° C. for 4-6 hours, and then pickled to obtain a coil. The coil is then cold rolled for 6-11 passes to obtain a thin coil. The thin coil is degreased and stretched and leveled to obtain a finished titanium strip.
2. The short-process cold rolling production process of titanium strip according to claim 1, characterized in that: The method for preparing the blank described in S1 comprises: S1-1, mixing, by mass percentage, 0.2-5% of molybdenum powder, 0.5-5% of vanadium powder, 0.5-2% of niobium powder and the remainder of titanium sponge to obtain a metal mixed powder; S1-2, dividing an aluminum foil sheet accounting for 3-6% of the mass ratio of the titanium sponge into two equal parts, and wrapping the two aluminum foil sheets with 0.2-1% of tin powder, 0.2-0.8% of zirconium powder, and 0.2-0.6% of hafnium powder, accounting for the mass ratio of the titanium sponge, to obtain two packages; S1-3, divide the metal mixed powder into three parts, and the mass ratios of the three parts of the metal mixed powder are: 0.3~0.7:1:0.3~0.7; introduce the first part of the metal mixed powder evenly into the mold, then add a part of the bagging material, and then evenly spread the second part of the metal mixed powder, and then add another part of the bagging material, and finally add the third part of the metal mixed powder; after pressing and forming, remove the mold to obtain a blank.
3. A short-process cold rolling production process for titanium strip according to claim 2, characterized in that: S1-1 The particle size of the molybdenum powder is 5 to 15 mm, the particle size of the vanadium powder is 4 to 8 mm; the particle size of the niobium powder is 3 to 6 mm; and the particle size of the sponge titanium is 5 to 10 mm.
4. The short-process cold rolling production process of titanium strip according to claim 1 is characterized in that: S1-2 The package size matches the size inside the mold; the particle size of the tin powder is 0.5-2 mm; the particle sizes of the zirconium powder and hafnium powder are both 0.5-3 mm.
5. The short-process cold rolling production process of titanium strip according to claim 1, characterized in that: The sintering temperature of the vacuum sintering in step S2 is 1800-2200°C, and the vacuum degree is 0.1-1×10 -2 Sintering under Pa conditions for 5 to 8 hours.
6. The short-process cold rolling production process of titanium strip according to claim 1, characterized in that: The arc length of the vacuum consumable arc melting in S2 is controlled to be 160-180 mm, the melting current is 4000-5000 A, the melting voltage is 35-55 V, and the melting speed is 4-5 kg / min.
7. The short-process cold rolling production process of titanium strip according to claim 1, characterized in that: S3 The coil cold rolling is carried out by a twenty-roller cold rolling mill; and the deformation amount of the first pass is 25-35%, and the deformation amount of each subsequent pass decreases gradually, and the minimum deformation amount of the pass is 15-17%.
8. The short-process cold rolling production process of titanium strip according to claim 1, characterized in that: The annealing in step S3 is carried out in an argon atmosphere. During the heating process, the pressure in the furnace is 2-4 KPa and the argon flux is 30-50 m 3 / h, the pressure in the furnace is 0.8~1.2KPa and the argon flux is 15~25m 3 / h.
9. The short-process cold rolling production process of titanium strip according to claim 1, characterized in that: S3: The cold rolling speed is 100-120 m / min; the degreasing temperature is 50-70°C.
10. The short-process cold rolling production process of titanium strip according to claim 1, characterized in that: S3 The coil cold rolling is carried out by a twenty-roller cold rolling mill; and the deformation amount of the first pass is 25-35%, and the deformation amount of each subsequent pass decreases gradually, and the minimum deformation amount of the pass is 15-17%.
